GAMIFICATION IN MARKETING: A SYSTEMATIC LITERATURE REVIEW OF TRENDS AND DEVELOPMENTS - Safarudin Hisyam Tualeka (Ikatan Dosen Menulis, 2026)
As gamification becomes an increasingly essential strategy to enhance customer engagement and brand loyalty, there remains a need for comprehensive reviews of its academic landscape. This study aims to synthesize and analyze the trajectory of gamification research in marketing using a bibliometric analysis. Data was collected from the Scopus database, comprising peer-reviewed articles published between 2010 and 2022, and analyzed using the bibliometrix R package. The analysis reveals a steady growth in publications, highlighting influential authors and foundational articles. Furthermore, the findings identify five major thematic clusters: marketing and consumer engagement, psychological foundations, education, digital integration, and sustainability. The study concludes that gamification is a versatile tool extending beyond commercial marketing into broader social impacts. Future research should focus on cross-disciplinary collaborations and leveraging emerging technologies to address societal outcomes.